Menyoal Efektivitas Asas Erga Omnes Dalam Konsep Eksekutorial Dan Hukum Islam (Studi Putusan MK Nomor 91/PUU-XVII/2020) - Armanda, Rizki; Abdurrofiq, Atep (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2024)
The validity of the erga omnes principle is reflected in the provision stating that the Constitutional Court's decision can be implemented directly without any consideration of the decision of the relevant authorized official unless other regulations and laws regulate it. This provision reflects the binding legal force and comprehensive nature (between parties), which generally applies to the parties to the case. Problems arise when the Constitutional Court's decision is not implemented by the parties to the case, state institutions, state administrators, and related parties for various reasons. This research is a normative legal research with secondary data. The results of the study show that the logistical consequences of the erga omnes principle, which requires all levels of citizens to implement the decision, impact parties with various interests so that they feel disadvantaged. In a situation like this, the parties can no longer take other legal measures except to obey and comply with the punishment.